Split-skin-graft wrapped conformer to treat severe contracted sockets - Al Hasan, Sultan; Galindo-Ferreiro, Alicia; Bigethi, Carolina [UNESP]; Meneghim, Roberta L.S.F. [UNESP]; Al Shaikh, Osama; Schellini, Silvana A. [UNESP] (Wolters Kluwer, 2018)
This case series present the surgical management of cases with severe contracted sockets using a split-skin-graft wrapped conformer. Eight patients with severely contracted anophthalmic sockets underwent surgery. The surgical technique is described and a chart review was performed to collect patient data pre- and postoperatively. Preoperatively, all patients had grade 3 or 4 contracted sockets with shallow or obliterated fornices and patients were unable to retain an external prosthesis in place. Donor material was harvested from the supraclavicular area. The split-skin-graft was successfully performed in all cases without fornix-deepening sutures. All patients underwent a significant improvement of socket contracture enabling retention of the prosthesis and were satisfied with the outcomes. The split-skin-graft wrapped conformer is a rapid and less surgically challenging option to correct severe contracted anophthalmic sockets.
Keywords: Anophthalmic socket; Contracted anophthalmic socket; Split-skin-graft; Wrapped conformer